2018
DOI: 10.4103/sajc.sajc_18_17
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of weekly versus three-weekly paclitaxel plus platinum neoadjuvant chemotherapy in patients with locally advanced squamous cell head and neck carcinoma: A pilot study

Abstract: Background:Squamous cell carcinoma of head and neck (SCCHN) is one of the most common cancers seen in India and also the world. Majority of patients present in locally advanced (LA) disease where neoadjuvant combination chemotherapy with a taxane plus platinum with/without 5-Fluorouracil is the standard of care treatment. There are no/few prospective trials of weekly paclitaxel in SCCHN in spite of convincing evidence regarding safety and tolerability in other solid tumors such as breast, ovary, and lung carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Chemotherapy (dacarbazine, temozolomide, cisplatin and taxol) is mostly used for pre and postoperative adjuvant-therapy [16][17][18][19][20]. Studies related to carcinoma of breast and lungs have been reported [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy (dacarbazine, temozolomide, cisplatin and taxol) is mostly used for pre and postoperative adjuvant-therapy [16][17][18][19][20]. Studies related to carcinoma of breast and lungs have been reported [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Our study is novel in that it assesses low‐dose PCC. Owing to its different mechanism of action, toxicity profile and radio‐sensitising activity, low‐dose PCC may be more tolerable for patients with suboptimal performance status 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…Owing to its different mechanism of action, toxicity profile and radio-sensitising activity, low-dose PCC may be more tolerable for patients with suboptimal performance status. [6][7][8] The objective of our study is thus to evaluate the tolerability and efficacy of low-dose PCC, which could be an attractive treatment option for metastatic or unresectable HNSCC patients who are not candidates for checkpoint inhibitors, 5-FU and/or high-dose chemotherapy regimens.…”
mentioning
confidence: 99%